Analisis Tingkat Kesulitan Soal Pemecahan Masalah dalam Buku Siswa Pelajaran Matematika SMP Kelas IX Kurikulum 2013 - Utami, Rizky Danu, Idris Harta, M.A., Ph.D (2017)
This study aims to analyze and describe the level of difficulty of problem solving items in the mathematicstextbook forninth-gradeof curriculum 2013 reviewed of the components of problem solving itemsincludethattypes of number, types of operation,amount of operations, amount of problems/questions, the adequacy of data, and like-beforequestion. This research was qualitative. The object of this study is the mathematicstextbook forninth-gradeof curriculum 2013 for 1st and 2nd semester in 2015 published by the Ministry of Education and Culture. Questions analyzed include problems solving items in the example problems, exercises, and competencetest. Data accumulation techniques by determine of problem solving items in mathematics textbooks. Data analysis techniques are data reduction, data presentation, and conclusion. The results showed that problem solving items in this book in terms of the types of numbers and a lot of problem the level of difficulty is easy; in terms of the types of operations, the adequacy of the data, and the like-before problems problem the level of difficulty is fare or medium; as well as in terms of amount of operations problem the level of difficulty is high. This means problem solving items in this book can practice counting skills and master the mathematical concepts in a variety of problems.